Deformation and lifespan of a polyethylene pipe - Dubey Nikita Abhay (2014)
Gas transport has evolved from using metallic pipes in the past to polymer pipes nowadays. Advantages like cost and corrosion-resistant properties have made polymer pipes to be the preferred choice amongst gas transmission and distribution businesses. Generally, to stop the gas flow in the pipe during emergency situations or routine repair work, a squeeze-off procedure is employed on polyethylene pipes. In this procedure, a damaged pipe is first isolated by pinching the walls of the pipe to stop the gas flow. Once the flow has stopped, repair work will be carried out. However, the mechanical activity of adding a load on the walls of the pipe causes degradation of the pipe. This damage can potentially be extremely hazardous. There have been several pipe explosions in the world where the squeeze-off procedure was believed to be responsible. The objective of this project is to understand the effect of squeezing (and re-rounding) on the properties of the pipe, particularly, yield strength. The criterion placed by Singapore Power (SP) is that a pipe should maintain a minimum strength of 10 MPa after 50 years. This report shows that when the pipes undergo the squeeze-off procedure more than once around the same region, they fall below the criterion and therefore are not considered useful any longer. Hence, it is concluded that the pipes should not undergo more than 1 squeeze at a given location on the pipe.